Allu tells more stories - Pavel Allu; Valentina Dedyk (Alexander King, 2013)
Allu tells more stories. Ambient audio for video session, including set-up conversation and conversation between Allu and Valya as King puts away gear. Works in Institute for Advanced Teacher Training, Palana. She was born in a yaranga on the tundra.